2011
DOI: 10.1590/s1415-47572011005000046
|View full text |Cite
|
Sign up to set email alerts
|

Positive selection, molecular recombination structure and phylogenetic reconstruction of members of the family Tombusviridae: implication in virus taxonomy

Abstract: A detailed study of putative recombination events and their evolution frequency in the whole genome of the currently known members of the family Tombusviridae, comprising 79 accessions retrieved from the international databases, was carried out by using the RECCO and RDP version 3.31β algorithms. The first program allowed the detection of potential recombination sites in seven out of eight virus genera (Aureusvirus, Avenavirus, Carmovirus, Dianthovirus, Necrovirus, Panicovirus, and Tombusvirus), the second pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 40 publications
0
10
2
2
Order By: Relevance
“…Unlike previous dN/dS-based analyses of MCMV, we detected significant positive selection in the genome: at sites in P50, P32, and P31, three proteins of unknown function 45 . This can be attributed to the greatly increased volume of sequence data included in the analysis.…”
Section: /10contrasting
confidence: 99%
“…Unlike previous dN/dS-based analyses of MCMV, we detected significant positive selection in the genome: at sites in P50, P32, and P31, three proteins of unknown function 45 . This can be attributed to the greatly increased volume of sequence data included in the analysis.…”
Section: /10contrasting
confidence: 99%
“…Bootscan, Maxchi, LARD recombination events detected by only half of the nine methods in RDP4 were considered significant (25,26), and the results obtained by three programs, PHI test, Recco, and RDP4, were not consistent, we concluded that only limited HR occurred in sigB of Listeria sensu stricto.…”
Section: Resultsmentioning
confidence: 82%
“…PHI test was conducted in SplitsTree4 V4.14.2 (61). Recco (62) was used for the prediction of recombination events, recombinant sequences, and recombination breakpoints, as it uses a fast and sensitive algorithm (25). Parameter ␣, which represents the cost of mutation relative to recombination, yields additional information as to which sequence might be recombinant.…”
Section: Methodsmentioning
confidence: 99%
“…These findings indicate that the MNSV CP gene could have been acquired through recombination. In this regard, tombusviruses and carmoviruses have been predicted to be highly recombinant compared with viruses of the other genera in the Tombusviridae family (Boulila, ). Moreover, recombination may occur between viruses belonging to different genera, particularly in the CP‐encoding gene (Boulila, ).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, tombusviruses and carmoviruses have been predicted to be highly recombinant compared with viruses of the other genera in the Tombusviridae family (Boulila, ). Moreover, recombination may occur between viruses belonging to different genera, particularly in the CP‐encoding gene (Boulila, ). Such a recombinant event has been studied extensively for CNV and MNSV (Riviere and Rochon, ).…”
Section: Discussionmentioning
confidence: 99%